Computational human head models of tDCS: Influence of brain atrophy on current density distribution - Mahdavi, Shirin; Towhidkhah, Farzad (Brain stimulation, 2018)
Despite increasing attention to the application of transcranial Direct Current Stimulation (tDCS) for enhancing cognitive functions in subjects exposing to varying degree of cerebral atrophy such as Alzheimer's disease (AD), aging, and mild cognitive impairment (MCI), there is no general information for customizing stimulation protocol. The objective of this study is to examine how cerebral shrinkage associated with cognitive impairment and aging can perturb current density distribution through the brain. We constructed three high-resolution human head models representing young, elder, and MCI subjects and modeled two electrode configurations using rectangular electrodes. Our results showed that decreasing gray matter volume in MCI, as well as aging, reduced the magnitude of the current density in the brain compared to the young model. Also, morphology alterations of the cerebral sulcus could shape the vectors of the current density to flow in the depth of cortical regions by cerebrospinal fluid. This study provides a framework for further advanced studies in establishing new methodologies or modifying stimulation parameters. •We created computational human head models derived from corresponding MR images representing young, elder, and MCI subjects.•Large electrodes result in a wide distribution of current density regardless of healthy or patient head models.•Decreasing gray matter volume due to atrophy can alter the magnitude of the current density in the brain.•Cortical sulcus and fissures widening during the progress of atrophy play an important role in conducting current vectors.